A Portrait of Counselling: Counsellors’ Work Roles and Career Satisfaction - Smith, J. David; Drodge, Edward N. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper reports on a survey of counsellors who graduated from a Masters-level counsellor education program at a central-Canadian university. Within the context of a larger program evaluation, counsellors were asked to provide information about their work settings, professional activities, and clientele. They also provided information about how satisfied they are with several aspects of their careers in counselling. These data provide a portrait of counselling in the local community as a vibrant, dynamic profession adapting to the ever-changing social, political, and cultural context.